Reducing the Flow Distribution in Central-Type Compact Parallel Flow Heat Exchangers Having Optimized Tube Structure - Zhou, Jian; Ding, Ming; Meng, Zhaoming; Zhang, Yinxing; Sun, Zhongning (Frontiers in Energy Research, 2018)
Compact parallel manifolds are widely applied in flow heat exchangers. However, the flow maldistribution exists in the parallel manifolds when the flow is distributed in the header, because of the pressure maldistribution. For a heat exchanger, the uniformity of the flow distribution greatly influence the performance of the heat exchanger. It is significantly important to modify the design of the heat exchanger for a uniform flow distribution. In present study, to reduce the maldistribution in the manifolds, the numerical analysis has been made and a method by varying the insert length of tubes inside the header has been pointed out to solve this problem of flow maldistribution. To illustrate the reliability of this method to reduce the maldistribution, three base cases with different header diameters have been applied to be solved with the method. The results indicates that, by using the method, the maldistribution for three base cases can be reduced by 82% for the case1, 72% for the case2 and 68% for the case3. However, the insert length of tubes inside the header increases more pressure loss. The pressure drop for base cases are respectively increased by 2.83%, 4.83% and 6.46%. This method is proved to be effective under all flow rates.